2020
DOI: 10.1002/cncr.32926
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy and the risk of herpes zoster in patients with cancer

Abstract: Background The role and impact of radiation therapy (RT) on the development of herpes zoster (HZ) has not been well studied. The objective of this study was to investigate the association between RT and HZ. Methods A propensity score‐matched, retrospective cohort study was conducted using institutional cancer registry data and medical records from 2011 to 2015. The risk of developing HZ in the RT and non‐RT groups was compared using a Cox proportional hazards model. Associations also were explored between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Radiation could have been the trigger in our patient's case, but would not be expected to produce a multidermatomal, purpuric eruption. 10 It is the opinion of the authors that this is one of few reported cases of a patient with hemorrhagic herpes zoster associated with rivaroxaban, a selective inhibitor of clotting factor Xa.…”
Section: Discussionmentioning
confidence: 91%
“…Radiation could have been the trigger in our patient's case, but would not be expected to produce a multidermatomal, purpuric eruption. 10 It is the opinion of the authors that this is one of few reported cases of a patient with hemorrhagic herpes zoster associated with rivaroxaban, a selective inhibitor of clotting factor Xa.…”
Section: Discussionmentioning
confidence: 91%
“…A recent research showed that cancer patients receiving RT had a significantly higher risk of HZ (aHR: 2.59) compared with those who did not, particularly within the radiation field. Of note, HN cancers accounted for a small proportion in their cohort, and there was no difference in terms of the risk of HZ between them (18.5 vs. 5.8 per 1000 PYs for RT vs. non-RT group in HN cancers, p = 0.126) [ 9 ]. Another study focusing on patients with Hodgkin’s disease showed that the radiation field mattered.…”
Section: Discussionmentioning
confidence: 99%
“…Those with hematological malignancies had a higher possibilities of HZ development compared to ones with solid cancers [5][6][7][8]. For patients with a specific cancer diagnosis, the effect of different treatment modalities on risk of HZ has not been well understood [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first populationbased study to investigate the relationship between radiotherapy and the incidence of herpes zoster in oral cavity cancer patients. In 2020 and 2021, there were two articles that investigated the relationship between head and neck cancer and herpes zoster (11,12); however, these studies did not perform a subgroup analysis for oral cavity cancer. The clinical behavior is different in each type of head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%